Fishing ground forecast in the offshore waters of CentralVietnam (experimental results for purse-seine and drift-gillnet fisheries) - Bo, Doan; Cau, Le Hong; Thanh, Nguyen Duy (VNU Journal of Science: Earth and Environmental Sciences, 2010)
Abstract. This paper specifies that research, analysis and estimate on marine environmental and biological conditions are very important for fishing ground forecast in offshore waters. The multi-variate regression equations among Catch Per Unit Efforts (CPUE), temperature structures and primary production have been established and used for monthly fishing ground forecast for purse-seine and drift-gillnet fisheries in the offshore waters of centralVietnam. The experiment forecast result in May, June and July, 2009 presented up to 60 percentage of acception. Meanwhile, the quantity of good forecasts are about 50% and the quantity of excellent forecasts ranks from 25 to 41%. The Length base Cohort Analyis (LCA) and Thompson and Bellmodels have been used for annual fishing ground forecast for Skipjack tuna ( Katsuwonus pelamis ) population, which is main object of drift-gillnet fishery. The forecast results showed that when yield in 2009 is 17,831 tonnes, its biomass in early that year is 111,906 tonnes and its forecast yield in 2010 is 18,211 tonnes. If the fishing effort in 2009 is X=1.0, its value of MSY (19,319 tonnes/year) will be gained corresponding to X=2.0. Keywords: Fishing ground forecast, offshore waters, purse-seine fishery, drift-gillnet fishery